1984
DOI: 10.1139/v84-199
|View full text |Cite
|
Sign up to set email alerts
|

Glycosides from Muscaricomosum. 5. Structure of muscaroside B

Abstract: A further component of the glycoside mixture extracted from the bulbs of Muscaricomosum has been completely characterized by chemical degradative study and spectral investigation. This glycoside, 2, termed muscaroside B, possesses an α-L-arabinofuranosyl(1 → 2)-α-L-arabinopyranosyl(1 → 3)[α-L-rhamnopyranosyl(1 → 2)]-β-D-glucopyranosyl(1 → 2)-α-L-arabinopyranosyl(1 → 6)-β-D-glucopyranosyl chain linked at the 3-position of eucosterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In connection with our studies (1)(2)(3)(4)(5) on the glycoside fraction of Muscari comosum we recently reported the isolation and structure determination of muscarosides A (4) and B (5). In this paper we describe the structure elucidation of a minor glycoside, muscaroside C, 1, which possesses a P-D-apio-Dfuranosyl( 142)-P-D-glucopyranosyl-(1-2)-a-L-arabinopyranosyl(l+6)-P-D-glucopyranosyl chain linked at the 3-position of (23S)-17,23-epoxy-3~,30,31-trihydroxy-27-nor5a-lanost-8-ene 2 (2).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…In connection with our studies (1)(2)(3)(4)(5) on the glycoside fraction of Muscari comosum we recently reported the isolation and structure determination of muscarosides A (4) and B (5). In this paper we describe the structure elucidation of a minor glycoside, muscaroside C, 1, which possesses a P-D-apio-Dfuranosyl( 142)-P-D-glucopyranosyl-(1-2)-a-L-arabinopyranosyl(l+6)-P-D-glucopyranosyl chain linked at the 3-position of (23S)-17,23-epoxy-3~,30,31-trihydroxy-27-nor5a-lanost-8-ene 2 (2).…”
supporting
confidence: 73%
“…No direct evidence for the a-configuration of the L-arabinopyranosyl unit was found, owing to its high conformational mobility (4,5,17). However, an a-configuration was inferred from the striking similarity between the I " data of the L-arabinopyranosyl unit of 1 and those found for the a-L-arabinopyranosyl residues identically located in muscarosides A and B (4, 5).…”
mentioning
confidence: 97%
“…Klyne's rule; [12,14] the application of which firmly indicated a -configuration for E (Table 3). In fact, the two alternative combinations (obtained by supposing the presence of residue E with -or -configuration in the pentasaccharide chain) gave calculated [M] D values of -22.1°for the -configuration of E and +166.7°for the -configuration of E Ϫ both of which differ considerably from the observed value of 192.2°.…”
Section: Structural Elucidation Of Acid Hydrolyzed Product (Os)mentioning
confidence: 99%
“…[12,14] These methods overcame the problems associated with the lack of monosaccharide references and the difficulties associated with its isolation. Lipkind et al [9] exploited the relative intensities of the inter-residual NOE effects by analyzing the structural and stereochemical factors determining the conformation of the glycosidic linkages; data showed that the main structural factors determining the NOE and the preferred conformation in disaccharide units were the configuration of the glycosidic linkage, the nature of the sugar, the position of glycosidation, and the absolute configuration of the constituent residues.…”
Section: Structural Elucidation Of Acid Hydrolyzed Product (Os)mentioning
confidence: 99%
“…76,[81][82][83][84] Extensive work on the bulbs by Adinol et al resulted in the isolation of the free aglycones present in the bulbs (20,21,22,54,(169)(170)(171)(172)(173)(174)(175) [85][86][87][88][89] as well as the full structural elucidation of the glycosides (86, 87, 102, 103 and 176). [90][91][92][93][94] All the nortriterpenes isolated from Leopoldia comosa mentioned so far have S conguration at C-23, three compounds with R conguration have also been identied, 177, 91 178 (23R 20) and 179 (23R 170). 89 Two classes of homoisoavanones have been isolated from the bulbs of L. comosa, the 3-benzyl-4-chromones (30, 58, 59, 61, 62, 80, 97, 180-181) 95,96 and the scillascillin type (55, 104-107 and 182).…”
mentioning
confidence: 99%